CAN INDICATORS FROM ASSET GROWTH , DIVIDEND PAYOUT RATIO AND EARNINGS VOLATILITY M RESOLVE STOCK PRICE VOLATILITY PROBLEMS - Deni Sunaryo (Universitas Serang Raya, 2022)
This study aims to determine the effect of asset growth , earnings volatility and dividend payout ratio on stock price volatility in non-financial publicly listed companies on the Indonesia Stock Exchange for the 2018-2020 period. The data used are the financial statements of each sample company published on the website www.idx.co.id. The sampling method used is purposive sampling with a total sample of 58 companies. The analytical method used in this study is the causality method, with classical assumption testing, as well as multiple linear regression statistical analysis using SPSS version 25. Based on the results of the study, it can be concluded that partially only asset growth has an effect on stock price volatility. Meanwhile , earnings volatility and dividend payout ratio have no effect on stock price volatility. However, simultaneously asset growth, earnings volatility and dividend payout ratio have an effect on stock price volatility.